(untitled) (Literary Voice, 2024)
This paper essays to trace out the ecofeminist perspectives which inform Kamala Markandaya’s The Coffer Dams. Markandaya is an ecofeminist novelist who makes Helen decipher the ecofeminst script of her novel. Helen considers the natives as human beings, and voices her feelings related to women and nature. She realizes that living with nature lends substance and authenticity to life. In spite of being dominated and exploited by her husband, Clinton, she fights against the patriarchal setup which exploits and oppresses both woman and nature.